2017
DOI: 10.1002/ese3.154
|View full text |Cite
|
Sign up to set email alerts
|

Status and future strategies for Concentrating Solar Power in China

Abstract: China is the world leader in several areas of clean energy, but not in Concentrating Solar Power (CSP). Our analysis provides an interesting viewpoint to China's possible role in helping with the market breakthrough of CSP. We present a short overview of the state-of-the-art of CSP including the status in China. A blueprint for China's CSP development is elaborated based on China's 13th 5-year program, but also on China's previous success factors in PV and wind power. The results of this study suggest that Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…66,67 The PV modules are composed of a number of PV cells that are series and/or parallel connected and the PV arrays are the same but made of PV modules instead of PV cells. Flat photovoltaic systems such as PV arrays and concentration photovoltaic systems (CPVs) are producing a large proportion of the solar electricity.…”
Section: Models For Solar Cell Combinationmentioning
confidence: 99%
See 1 more Smart Citation
“…66,67 The PV modules are composed of a number of PV cells that are series and/or parallel connected and the PV arrays are the same but made of PV modules instead of PV cells. Flat photovoltaic systems such as PV arrays and concentration photovoltaic systems (CPVs) are producing a large proportion of the solar electricity.…”
Section: Models For Solar Cell Combinationmentioning
confidence: 99%
“…Flat photovoltaic systems such as PV arrays and concentration photovoltaic systems (CPVs) are producing a large proportion of the solar electricity. 66,67 The PV modules are composed of a number of PV cells that are series and/or parallel connected and the PV arrays are the same but made of PV modules instead of PV cells. Based on the equivalent circuit diagram of a single diode model, it can be concluded that the PV modules also can be modeled by the same way.…”
Section: Models For Solar Cell Combinationmentioning
confidence: 99%
“…In 2001, the Chinese government proposed the energy system reform for the first time in the 10th Five-Year Plan in a bid to gradually optimize the energy structure, with a focus on reinforcing the power grid construction and actively developing hydropower ( Table 7). The government then released a series of policies to promote the rapid development of new energies [41,42]. The proportion of non-fossil energy consumption gradually increased from 8% in 2009 to 11% in 2014 in China, leading to a very apparent fluctuation in the substitution effect from 2010 to 2014.…”
Section: Energy Substitution Effectmentioning
confidence: 99%
“…According to statistics of the International Energy Agency shown (see Figure 3) Table 7). The government then released a series of policies to promote the rapid development of new energies [41,42]. The proportion of non-fossil energy consumption gradually increased from 8% in 2009 to 11% in 2014 in China, leading to a very apparent fluctuation in the substitution effect from 2010 to 2014.…”
Section: Energy Substitution Effectmentioning
confidence: 99%
“…Also, it can be easily coupled with a fossil fuel boiler to solve variability problem. Wang et al studied the future strategy for using concentrating solar power in China. Duan et al Simulated a solar collector connected to an auxilliary fossil fuel heater to generate power and reduce fossil fuel consumption.…”
Section: Introductionmentioning
confidence: 99%